The Relationship between Home Environmental Conditions and the Occurrence of Acute Respiratory Infection (ARI) in Toddlers in Nagan Raya Regency - Fera, Dian; Sriwahyuni, Susy (Universitas Teuku Umar, 2020)
Acute Respiratory Infection (ARI) is an infection that lasts up to 14 days. Most ARI are caused by infection, but can also be caused by inhalation of chemical and chemical substances. In 2018 the population was 3,885, with 342 children under five. The number of toddlers experiencing ARI is 218 toddlers. The purposes of this study were to determine the relationship of environmental conditions in the home with ARI in toddlers. This research uses analytic survey method with Cross Sectional approach. The study was conducted on August 20-September 5 2019, population 342 and sample of 77 peoples. The results showed there were a relationship among the house floor (P value 0.018